2018
DOI: 10.3892/or.2018.6940
|View full text |Cite
|
Sign up to set email alerts
|

Kenalog modified by ionizing radiation induces intrinsic apoptosis mediated by elevated levels of reactive oxygen species in melanoma cancer

Abstract: Kenalog is a synthetic glucocorticoid drug used to treat various cancers including ocular and choroidal melanoma. However, the drug achieves rarely sustainable results for patients. To overcome this difficulty, the structure of Kenalog was altered by ionizing radiation (IR) to develop a more effective anticancer agent for treatment of various skin cancers. The anticancer effect of modified Kenalog (Kenalog-IR) was assessed in melanoma cancer cells in vitro. The assessment of mitochondrial functions by MTT assa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…In a recent study, chrysin and luteolin showed improved anti-in ammatory activities in vitro and in vivo induced by γ-irradiation, and the chemical structure of hydroxyalkyl-substituted compounds was identi ed 12,21 . In addition, radiolytic transformation of alkaloids and steroids showed potent enhanced anti-cancer effects in melanoma, breast, liver, and lung cancer 11,[22][23][24][25] .…”
Section: Resultsmentioning
confidence: 99%
“…In a recent study, chrysin and luteolin showed improved anti-in ammatory activities in vitro and in vivo induced by γ-irradiation, and the chemical structure of hydroxyalkyl-substituted compounds was identi ed 12,21 . In addition, radiolytic transformation of alkaloids and steroids showed potent enhanced anti-cancer effects in melanoma, breast, liver, and lung cancer 11,[22][23][24][25] .…”
Section: Resultsmentioning
confidence: 99%
“…In the present study, IR-prednisolone significantly decreased the viability of liver cancer cells. As the percentage of apoptotic cells has been demonstrated to increase in numerous types of cancer cell following treatment with γ-irradiated drugs, it was hypothesized that IR-prednisolone may decrease the viability of liver cancer cells by promoting apoptosis and cell arrest (16). Evading apoptosis is a hallmark of cancer; potential anticancer drugs should therefore promote apoptosis (17).…”
Section: Discussionmentioning
confidence: 99%
“…Ionizing radiation is used to modify the structure of numerous drugs, and has been demonstrated to enhance their biological properties in vitro (13,14). Recent reports have demonstrated that γ-irradiation can create novel GC derivatives, such as γ-irradiated (IR)-dexamethasone (Dex-IR) and Kenalog-IR, the anticancer effects of which have been confirmed in vitro (15,16). To the best of our knowledge, however, the effects of γ-irradiation on prednisolone structure, and the mechanism by which it induces anticancer effects, have not yet been explained.…”
Section: Introductionmentioning
confidence: 99%
“…In a previous study, the authors irradiated rotenone with gamma rays and confirmed that its by-product, rotenoisin B, a radiolytic derivative, was produced, which inhibited proliferation in hepatocarcinoma (13). In addition, it was confirmed that radiation-irradiated Kenalog ® also increased the apoptotic effect of melanoma compared with Kanalog ® , the original material (14). To date, there are no reports on the effects of gamma irradiation on the amelioration of the pharmacological effects of NF.…”
Section: Introductionmentioning
confidence: 87%